Arab women writers : an anthology of short stories - Cohen-Mor, Dalya, 1948- (SUNY series, women writers in translation., 2005)
"Consisting of sixty short stories by forty women writers from across the Arab world, this collection opens numerous windows onto Arab culture and society and offers keen insights into what Arab women feel and think. The stories deal not only with feminist issues but also with topics of a social, cultural, and political nature. Different styles and modes of writing are represented, along with a diversity of techniques and creative approaches, and the authors present many points of view and various ways of solving problems and confronting situations in everyday life. Lively, outspoken, and provocative, these stories are essential reading for anyone interested in the Arab world."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved